A Comprehensive Comparison Study of Empirical Cutting Transport Models in Inclined and Horizontal Wells - Shiddiq, Asep Mohamad Ishaq; Christiantoro, Brian; Syafrie, Ildrem; -, Abdurrokhim; Marbun, Bonar Tua Halomoan; Wattimury, Petra; Resesiyanto, Hastowo (ITB Journal Publisher, LPPM ITB, 2017)
In deviated and horizontal drilling, hole-cleaning issues are a common and complex problem. This study explored the effect of various parameters in drilling operations and how they affect the flow rate required for effective cutting transport. Three models, developed following an empirical approach, were employed: Rudi-Shinduâs model, Hopkinsâ, and Tobennaâs model. Rudi-Shinduâs model needs iteration in the calculation. Firstly, the three models were compared using a sensitivity analysis of drilling parameters affecting cutting transport. The result shows that the models have similar trends but different values for minimum flow velocity. Analysis was conducted to examine the feasibility of using Rudi-Shinduâs, Hopkinsâ, and Tobennaâs models. The result showed that Hopkinsâ model is limited by cutting size and revolution per minute (RPM). The minimum flow rate from Tobennaâs model is affected only by well inclination, drilling fluid weight and drilling fluid rheological property. Meanwhile, Rudi-Shinduâs model is limited by inclinations above 45Â°. The study showed that the investigated models are not suitable for horizontal wells because they do not include the effect of lateral section.